UPAYA PENANGGULANGAN PENGANIAYAAN GURU - Sugianto - (Universitas Kapuas Sintang, 2020)
Efforts to tackle criminal abuse committed by parents of students against teachers that occur in schools both at the high school, junior high school and elementary school level. This aims to determine the efforts made by the school to tackle teacher maltreatment and to find out the factors that cause teacher maltreatment by parents of students, and to find out whether a new law is needed to provide protection for teachers and lecturers.Keywords: Efforts, Countermeasures,Persecution, Teachers.